2020
DOI: 10.5664/jcsm.8254
|View full text |Cite
|
Sign up to set email alerts
|

Association of sleep trajectory in adulthood with risk of hypertension and its related risk factors: the China Health and Nutrition Survey

Abstract: Peoples Republic of China; *Contributed equally Study Objectives: Few studies have examined the association between sleep duration trajectories and hypertension. This study aims to examine association of sleep duration trajectories with risk of hypertension and its related factors.Methods: This study used longitudinal data for 7,397 adults who provided valid responses in questionnaire with regard to information of sleep and hypertension from the China Health and Nutrition Survey (2004)(2005)(2006)(2007)(2008)(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…A study revealed that persistently slept ≤6 hours, compared with persistently slept 7 hours, increased the risk of hypertension among women in Korea through over 5 years follow-up; 20 another study conducted in China suggested persistently decrease of sleep duration was significantly associated with an increased risk of hypertension. 32 In consistent with the two findings, our results also observed that persistent short sleep duration increased the risk of hypertension. In addition, our findings found that persistently slept ≥10 hours/day and changed pattern over time also increased the risk of hypertension.…”
Section: Discussionsupporting
confidence: 91%
“…A study revealed that persistently slept ≤6 hours, compared with persistently slept 7 hours, increased the risk of hypertension among women in Korea through over 5 years follow-up; 20 another study conducted in China suggested persistently decrease of sleep duration was significantly associated with an increased risk of hypertension. 32 In consistent with the two findings, our results also observed that persistent short sleep duration increased the risk of hypertension. In addition, our findings found that persistently slept ≥10 hours/day and changed pattern over time also increased the risk of hypertension.…”
Section: Discussionsupporting
confidence: 91%
“…Another study found the association of persistent poor sleep quality and persistent sleep problems with continued deterioration in physical health [28]. Other studies have identi ed associations between persistently short nighttime sleep duration and the prevalence of hypertension [29], the risk of diabetes [27], and the risk of a rst cardiovascular event [17]. In addition, the Whitehall II study and a Korean study respectively found an association of consistently short sleep duration with the risk of dementia and depression [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies have shown that long-term sleep trajectories are unique predictors of health outcomes. For instance, consistent short and long sleep duration over time has been linked to multiple adverse health effects on human health, including systemic inflammation, type 2 diabetes, hypertension, and mortality [ 8 , 9 , 10 , 11 , 12 , 13 ]. Moreover, unstable or fluctuating sleep duration over time has been linked to increased risk of cardiovascular diseases and all-cause mortality [ 12 , 13 , 37 ], as well as elevated levels of inflammatory markers, such as C-reactive protein and interleukin-6 [ 10 , 11 ], which can contribute to many diseases, including coronary heart disease, stroke, and all-cause mortality [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, sleep is a dynamic behavior that may change over time. More recently, several studies suggested that changes in sleep and long-term sleep trajectories are unique predictors of health concerns and diseases, such as hypertension [ 8 , 9 ], systemic inflammation [ 10 , 11 ], cardiovascular events, and all-cause mortality [ 12 , 13 ]. Considering the important health implications of sleep patterns, it is important to study the factors that may shape sleep behavior and contribute to health outcomes.…”
Section: Introductionmentioning
confidence: 99%